"Don't mess with the Virgin": Iconoclastic art and popular censorship in Oruro (Bolivia) - Lavat, Baptiste (2021)
Censorship and the different ways of limiting or preventing freedom of expression constitute a multifaceted object of study with a long scientific trajectory. Several research works allow us to analyze it, either from a global theoretical framework or starting from a case study to illustrate it in a more concrete way. This article falls into this second category, starting from a specific situation to propose an analysis of some of the modes of application of censorship.   Given the contextual dimension of the case studied, the Oruro Carnival (Bolivia), we opted to present it from an essentially descriptive and critical perspective, without entering into theoretical or general considerations. To do this, we rely on field observations, as well as a series of press articles, which allow us to appreciate in a chronological way the censorship modalities that were intended to be applied against the work of artists who adopted a critical tone with Carnival. It was thus possible to demonstrate that the symbolic importance of this Bolivian holiday was on different occasions the pretext to justify a series of very aggressive reactions against those who questioned or criticized its organization and development.   Although it is based on a concrete and specific case, we consider that this work opens a space for reflection on the multiple forms that the will to censor people whose opinion and activity entail a critical dimension, susceptible to annoy or shock part of the opinion, can take public.